2013
DOI: 10.1097/jnn.0b013e31828a40f6
|View full text |Cite
|
Sign up to set email alerts
|

What Brain Tumor Patients and Their Families Have Taught Me

Abstract: The purpose of this article is to identify the experience of the patient with a World Health Organization grade III/IV and IV/IV brain tumor, and that of their family, to best understand how to treat them. It is the cumulative input of hundreds of patients and family members seen over a 20-year career of specialization at two teaching hospitals. No patient who has been diagnosed with a brain tumor, whether low grade, high grade, or benign, escapes totally unharmed because tumor existence, surgical removal, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Beyond the area of brain injury, hope has been recognised as fundamental to the coping and adjustment of family members during critical and acute care (Keenan & Joseph, 2010), and in cases of brain tumours (Lucas, 2013). It has been documented as an essential factor enabling people with spinal cord injury to cope (Dorsett, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Beyond the area of brain injury, hope has been recognised as fundamental to the coping and adjustment of family members during critical and acute care (Keenan & Joseph, 2010), and in cases of brain tumours (Lucas, 2013). It has been documented as an essential factor enabling people with spinal cord injury to cope (Dorsett, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The need for hope is a prevalent theme in nearly all of the studies conducted on patients' experience of illness [6,7,9,11,12,20,21,26,[28][29][30]. It has been suggested that the initial and ongoing interaction between the patient and physician might provide patients with the greatest opportunity for retaining hope [10,20].…”
Section: Retaining Hopementioning
confidence: 99%
“…A powerful example of the needs of patients during this crucial time has been provided via patient and patientfamily interviews, which suggest patients fear an inevitable process of loss that is linked to the feeling of hope being taken away [11,13,17,26]. The most pervasive theme described by patients and family members at the time of diagnosis is the need to receive a hopeful message counterbalanced by reality, support and individualized information [7,10,[17][18][19][20][21]25].…”
Section: Communicating the Diagnosismentioning
confidence: 99%